A chronological model for the Late Paleolithic at Shuidonggou Locality 2, North China. - Fei Peng; Sam C Lin; Ilaria Patania; Vladimir Levchenko; Jialong Guo; Huimin Wang; Xing Gao (PLoS ONE, 2020)
The site of Shuidonggou Locality 2 offers important evidence for the Late Paleolithic sequence of north China. The site not only contains one of the earliest instances of ornamental freshwater shell and ostrich eggshell beads in the region, but also stone artifacts with features arguably resembling the Initial Upper Paleolithic (IUP) blade technology found farther north. The appearance of these innovative archaeological forms have been attributed to the arrival of hominin populations, possibly modern humans, into the region during Marine Isotope Stage 3. Yet, the chronology of the site remains debated due to ambiguities in the existing dates. In this study, we conduct a systematical radiocarbon analysis of charcoal and ostrich eggshell samples obtained throughout the site sequence. Both acid-base-acid and the more stringent acid-base-oxidation pretreatment methods were applied to the charcoal samples. The resulting ages follow an age-depth relationship that is consistent with the stratigraphic profile. In line with previous stratigraphic assessments, Bayesian age modeling suggests that site formation history can be split into two phases: an early phase 43-35 cal kBP associated with a lacustrine depositional environment, and a later phase 35-28 cal kBP associated with rapid terrestrial silt accumulation. The chronology of the archaeological layers containing IUP-like artifacts are placed at 43-39 cal kBP and 35-34 cal kBP respectively. This finding supports the interpretation that an IUP-like blade technology appeared in the SDG region by at least ~41 ka.